(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The possibility of obtaining high-quality porous agloporite material with high physical and mechanical properties based on local clay raw materials and industrial waste from the Tashkent industrial region has been established. The effect of chloride roasting, whose components are phosphogypsum industry waste and alkaline soda waste, on the mechanism and kinetics of mineral formation during agglomeration of agloporite gravel, is studied. It was established that the used waste - mineralizers accelerate the process of glass formation during chloride firing, reducing the temperature of agglomeration and pressing by 50-80 oС, while obtaining a durable porous material. The regularities of the influence of physicochemical features, used clay materials and flotation waste of the Almalyk mining and smelting complex on the mechanism of mineral and pore formation during agglomerate agglomeration are revealed.